2004
DOI: 10.1093/treephys/24.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Trophic control of bud break in peach (Prunus persica) trees: a possible role of hexoses

Abstract: Vegetative buds of peach (Prunus persica L. Batsch.) trees act as strong sinks and their bud break capacity can be profoundly affected by carbohydrate availability during the rest period (November-February). Analysis of xylem sap revealed seasonal changes in concentrations of sorbitol and hexoses (glucose and fructose). Sorbitol concentrations decreased and hexose concentrations increased with increasing bud break capacity. Sucrose concentration in xylem sap increased significantly but remained low. To clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 40 publications
4
72
1
2
Order By: Relevance
“…CWAI activity may be inversely correlated to the sucrose concentration and positively correlated with the glucose and fructose concentrations in the sink tissues (Ito et al, 2002). Maurel et al (2004a) found an increase in CWAI activity in peach buds just before the leafing in natural conditions, but when branches were maintained under chilling privation this activity remained low.…”
Section: Resultsmentioning
confidence: 98%
“…CWAI activity may be inversely correlated to the sucrose concentration and positively correlated with the glucose and fructose concentrations in the sink tissues (Ito et al, 2002). Maurel et al (2004a) found an increase in CWAI activity in peach buds just before the leafing in natural conditions, but when branches were maintained under chilling privation this activity remained low.…”
Section: Resultsmentioning
confidence: 98%
“…Although starch provides a major reserve of carbohydrate in deciduous woody plants and can enhance cold hardiness via hydrolysis to soluble sugars (Morin et al, 2007), starch content in the shoots was not correlated with seasonal changes in cold hardiness in either cultivar (Table 1). Analyses of the composition of xylem sap in peach trees indicate that hexoses (glucose and fructose) are present in addition to sorbitol and sucrose (Maurel et al, 2004a). González-Rossia et al (2008) reported that sorbitol, fructose, and glucose were the main sugars induced in bark tissues by artificial chilling, whereas sucrose was present at the lowest quantities in various Prunus species.…”
Section: Discussionmentioning
confidence: 99%
“…The starch concentration has been found to increase under stressful conditions and decline in favorable environments (Zhang et al, 2008;Duan et al, 2014). C remobilization from a stored C pool has been demonstrated to be an important process during bud burst (Maurel et al, 2004) and root formation (Maillard et al, 2001). Although a part of stored NSC (including starch) was sequestered, the rest, even when blocked for several years, can be remobilized to support recovery from severe disturbances.…”
Section: Storage and Growthmentioning
confidence: 99%